Application of the Green Building Concept (BGH) in High-Rise Office Buildings Based on Hybrid Dynamics to Improve Cost Performance - Barri, Ahmad (ASTONJADRO, 2024)
This research aims to determine the application of the green building concept (BGH) in multi-story office buildings based on hybrid dynamics to improve cost performance. The method used in this research is a quantitative method with primary and secondary data types. The sampling technique used purposive sampling with 163 individuals involved in the Ginza Business Loft Jababeka area. The data management and analysis techniques used are outer model analysis (measurement model) and inner model analysis (structural model) using the SmartPLS 3 Multivariate Structural Equation Model (SEM) technique. Partially, the results of this research show that X2.2.21 has a P-Values value of 0.000 for X2.2 has a P-Values value of 0.000 on 0.000, it can be concluded that X3.2.2 has a strong influence on variable X3.2 in the model. The variable X2.3.6 also has a P-value value of 0.000, meaning that X2.3.6 has a significant effect on variable X2. Variable X3.1.6 has a P-value of 0.000 for variable X3, indicating that the auditor quality variable has a significant effect on variable X3. Furthermore, variable Y2.2 has a P-value value of 0.000, indicating that this variable has a significant influence on variable Y2. These results illustrate that variable Y2.2 has a strong influence on variable Y2 in the context of the research model. Overall, the results of the P-Values analysis show that the variables mentioned above have a significant influence on the variables measured.